Sistem Prediksi Jumlah Produksi Tahu Takwa Menggunakan Metode Fuzzy Tsukamoto Berbasis Web - Bagus Dwi Prasetya; Syaputri, Rika Wahyu; Annisa, Fera; Wardana, Aldestra Bagas; Farida, Intan Nur (Generation Journal, 2023)
Takwa Popular Tofu Factory still uses estimates of the amount of production with no accurate calculation and computer technology. Therefore, the calculation system of the tsukamoto fuzzy method with a web-based concept is expected to minimize losses due to the amount of production that is not in accordance with market share. This study aims to assist the Takwa Popular Tofu factory in estimating the amount of daily production in accordance with market share. The test results using Mean Absolute Percentage Error (MAPE) show the accuracy of the system calculation of 95.90% with an error value of 4.09 so that the interpretation of the MAPE value is accurate.